Theoretical analysis and pressure distribution of thin-walled metal inverbuckle energy absorbing tubes - Chirwa, Efford Clive (Cranfield University, 1998)
This dissertation presents an investigation in the energy absorbing capacity of thin-walled metal inverbucktubes loaded in axial compression. It also presents the inversion-buckling(curling-buckling) behaviour achieved in both, quasi-static and dynamic loading conditions. In addition, for the first time, the experimental results of the pressure or normal stress distribution between the inside surface of the inverbucktube and die fillet radius interface are stipulated. These were very successful, using the pressure transducer method. Furthermore, a mathematical model has been developed, based on theory of plasticity and making use of energy method. This predicts the amount of energy absorbed in the assumed seperate collapse processes. Results yielded from the theory, showed good agreement with the experimental results which had geometry factor within feasibility boundaries of inverbuckling collapse (6.5 ( 5/2t,, ( 22.5). The successful prediction of energy absorbed, inverbuckling load and pressure distribution, not only proves the validity of the model, but also confirms the quality of the modelling approach proposed in this dissertation. Using this mathematical model, inverbucktubes could be designed, developed and applied.